An implementation evaluation of a policy aiming to improve financial access to maternal health care in Djibo district, Burkina Faso - Belaid Loubna; Ridde Valéry (BMC, 2012)
Abstract Background To bring down its high maternal mortality ratio, Burkina Faso adopted a national health policy in 2007 that designed to boost the assisted delivery rate and improving quality of emergency obstetrical and neonatal care. The cost of transportation from health centres to district hospitals is paid by the policy. The worst-off are exempted from all fees. Methods The objectives of this paper are to analyze perceptions of this policy by health workers, assess how this health policy was implemented at the district level, identify difficulties faced during implementation, and highlight interactional factors that have an influence on the implementation process. A multiple site case study was conducted at 6 health centres in the district of Djibo in Burkina Faso. The following sources of data were used: 1) district documents (n = 23); 2) key interviews with district health managers (n = 10), health workers (n = 16), traditional birth attendants (n = 7), and community management committees (n = 11); 3) non-participant observations in health centres; 4) focus groups in communities (n = 62); 5) a feedback session on the findings with 20 health staff members. Results All the activities were implemented as planned except for completely subsidizing the worst-off, and some activities such as surveys for patients and the quality assurance service team aiming to improve quality of care. District health managers and health workers perceived difficulties in implementing this policy because of the lack of clarity on some topics in the guidelines. Entering the data into an electronic database and the long delay in reimbursing transportation costs were the principal challenges perceived by implementers. Interactional factors such as relations between providers and patients and between health workers and communities were raised. These factors have an influence on the implementation process. Strained relations between the groups involved may reduce the effectiveness of the policy. Conclusions Implementation analysis in the context of improving financial access to health care in African countries is still scarce, especially at the micro level. The strained relations of the providers with patients and the communities may have an influence on the implementation process and on the effects of this health policy. Therefore, power relations between actors of the health system and the community should be taken into consideration. More studies are needed to better understand the influence of power relations on the implementation process in low-income countries.